Metaphors of Animal Names in Indonesian - I Dewa Putu Wijana (Deskripsi Bahasa, 2018)
This article concerns with the use of metaphors for constructing animal names in Indonesian. By using data collected from Indonesian Standard Dictionary and cognitive metaphorical theory, it is found that the animals names can be expressed in various forms and the metaphors are possibly placed on the head, attribute, or the whole of construction. The source domains of the metaphors are taken from entities that exist in the speakers’ environment and they are projected to the target domains through similarities and associations. As result of, Indonesian relation to other languages, the influence of foreign languages and local languages in the formation of metaphors cannot be avoided.